PROMOTIONAL COMMUNICATION AND REFELIXIVITY: CASE STUDIES IN THE MEDIA POLITICS AND PROBLEMATIZATION OF NEO-LIBERALISM - Greenberg, Joshua L. (My University, 2003)
This dissertation offers a critical analysis of the media politics underlying the shift to neo-liberalism. Special attention is paid to the relationships between news media, government and corporate public relations, and social movement activism in the context of changing policy priorities that advance market-based solutions for economic and political challenges. Neo-liberalism is accounted for in terms of both its policy and ideological dimensions, and the study demonstrates that neo-liberal forms of rule contribute to, rather than alleviate, risk and uncertainty. The consequence or 'reflexive effect' of this is a re-politicization of the public sphere and the creation of a space for struggle over the allocation of blame and responsibility for the social harms such policy programmes frequently entail. Such struggles, the study argues, tend to be waged communicatively and in the arena of news media. The research draws on a range of theoretical and methodological approaches to the study of media and politics, obtaining insight from the disciplines of sociology, political science, media studies, management communication and policy studies. Quantitative and qualitative approaches, including content and textual analysis, openended interviews, and various forms of observational analysis (participant and nonparticipant), are used in an effort to explain the various dimensions of neo-liberal rule and resistance. The research demonstrates that media production sites are less closed to the participation and contributions of marginalized sources than critical studies have previously suggested. At the same time, however, asymmetrical power relations imbue both policy and news making, and while alternative actors may be successful in having their voices heard, this is not the same thing as arguing that the media and policy fields are necessarily open to alternative viewpoints. Indeed, in the cases examined here, a liberal market ideology was shown to be predominant, despite the strategies and activities of social movements and occasional failures of elites to control the parameters of policy debate. Empirical evidence for these findings is provided in two case studies, each of which contains a critical news analysis and examination of the PR strategies and positions of key policy participants. The first study interrogates the issue of market-based electricity restructuring in Ontario under the Conservative governments of Mike Harris and Ernie Eves (1995-2002). The second study investigates debates that have occurred over global labour standards in relation to the rise of commodity chain production within the sports footwear and apparel industry and addresses exclusively the anti-sweatshop campaign against Nike.
Keywords: Sociology; Sociology